Interplay of edge/screw dislocations and enhanced magnetism in exfoliated pyrolytic graphite with distorted hexagonal moiré superlattices - Filippo S. Boi; Shanling Wang; Wenxue Li; Omololu Odunmbaku; Shuai Gao; Jian Guo; Jiaxin Song; Jiqiu Wen; Hong Zhang (Carbon Trends, 2021)
The recent observation of enhanced magnetic signals in post-exfoliated lamellae of highly oriented pyrolytic graphite (HOPG) has attracted an important attention. It has been suggested that such a magnetization enhancement may originate from exfoliation-induced structural transitions, possibly involving rhombohedral domain and/or topological disorder formation. Further studies are therefore needed in order to elucidate the origin of such magnetic effects. Here we report a novel investigation on the structural and magnetic properties of multiple lamellae exfoliated from the inner regions of a main HOPG sample. HRTEM revealed moiré-superlattices with coexisting-periodicity-gradients ∇D∼13.1 nm to 16.2 nm, D∼ 2.6 nm in lamella-1, ∇D∼ 30 nm to 36 nm in lamella-2 and ∇D∼ 10.4 nm to ∼ 12.0nm, 3.1 nm in lamella-3. Exfoliation-induced distortion effects of the moiré-areas were investigated by employing HRTEM and Fourier transform analyses. We describe this effect on the basis of the Burgers–Bragg–Read–Shockley model with contributions arising from both I) edge dislocations (tilting angle θc ≠ 0, altered by the tape-exfoliation) and II) screw dislocations (twisting angle θtwist ≠ 0). Extended temperature dependent electron paramagnetic resonance (T-EPR) investigations revealed important shifts in the position of the π-electron differential absorption feature. The reported results are possibly an indicator of defect-induced electron correlation effects. Superconducting quantum interference device (SQUID) magnetometry measurements revealed an unusual magnetization-enhancement interpreted as a consequence of the exfoliation process.